Unleashing Gastronomy Potential for Tourism Product Diversification in Labuan Bajo Manggarai Barat - Fransiskus Xaverius Teguh; Amelda Pramezwary; Wilhelmina Rose Gajeng (E-Journal of Tourism, 2025)
This study explores how local gastronomy can diversify tourism products in Labuan Bajo, Manggarai Barat, a destination dominated by nature-based attractions. Using a qualitative case study, data were collected from 25 informants (local chefs, entrepreneurs, operators, community leaders, government) through 15 in-depth interviews and 2 focus group discussions, complemented by participant observation. Thematic analysis identified four key themes: (1) authenticity and cultural identity embedded in local dishes, (2) stakeholder collaboration gaps, (3) limited culinary promotion and infrastructure, and (4) emerging grassroots innovations. Findings show that while tourists value unique dishes such as jagung titi and se’i, their integration into tourism remains fragmented; collaborative events and culinary SMEs demonstrate potential models for scaling. The novelty of this study lies in mapping stakeholder collaboration mechanisms and proposing a staged experience model (education, taste exploration, cultural celebration) tailored for Labuan Bajo’s gastronomy sector. Integrating gastronomy into tourism strategies can extend visitor stays, strengthen local identity, and foster inclusive economic growth.